2017
DOI: 10.1111/gcb.13622
|View full text |Cite
|
Sign up to set email alerts
|

Tree range expansion in eastern North America fails to keep pace with climate warming at northern range limits

Abstract: Rising global temperatures are suggested to be drivers of shifts in tree species ranges. The resulting changes in community composition may negatively impact forest ecosystem function. However, long-term shifts in tree species ranges remain poorly documented. We test for shifts in the northern range limits of 16 temperate tree species in Quebec, Canada, using forest inventory data spanning three decades, 15° of longitude and 7° of latitude. Range shifts were correlated with climate warming and dispersal traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 41 publications
7
89
1
Order By: Relevance
“…Thus, our results suggest that range shifts of most tree species will not keep pace with climate change. This finding is in line with many previous studies that suggest most of tree species will not move fast enough to track and adjust to the pace and magnitude of climate change (Sittaro et al., ) and biotic factors (e.g. dispersal, colonization) dominate the leading edge limits (Putnam & Reich, ; Saltré, Duputié, Gaucherel, & Chuine, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, our results suggest that range shifts of most tree species will not keep pace with climate change. This finding is in line with many previous studies that suggest most of tree species will not move fast enough to track and adjust to the pace and magnitude of climate change (Sittaro et al., ) and biotic factors (e.g. dispersal, colonization) dominate the leading edge limits (Putnam & Reich, ; Saltré, Duputié, Gaucherel, & Chuine, ).…”
Section: Discussionsupporting
confidence: 91%
“…However, we found that tree harvest generally did not interact with climate change to facilitate or ameliorate extinctions. This was because tree species may take centuries to respond to changing climates due to inherent demographic inertia that enables tree species resist extinction during unfavourable climatic conditions (Sittaro et al., ). As a result, our 100‐year simulation period may not be long enough for interactive effects to manifest.…”
Section: Discussionmentioning
confidence: 99%
“…The latitudinal shift patterns we observed for four northern temperate hardwood tree species were generally consistent with climate change predictions of northward shifts at the northern range limit (Périé & de Blois, ) and with those of previous studies (Boisvert‐Marsh et al, ; Sittaro et al, ). They also reveal shifts that result from spatially explicit responses, with different combinations of climate change and disturbance variables influencing the probability of sapling occurrence gains depending on location within the study area.…”
Section: Discussionsupporting
confidence: 90%
“…Recent research found that the rate of tree species latitudinal migrations were, on average, <50% of that required to keep pace with the spatial velocity of climate change [31] suggesting that migration success of individual species will require active management. The management of Tsuga canadensis in particular, may include site preparation [30] and the removal of the pervasive competitor, Fagus grandifolia saplings, which are shade tolerant and also susceptible to beech bark disease [5].…”
Section: Discussionmentioning
confidence: 99%